Strategies described in relation to the teaching and learning of Chemistry involving students with Hearing Impairment registered in SIMPEQUI(s) - (2006-2021) (Research, Society and Development, 2022)
This article aims to map the scientific production presented in the form of works, presented at the event of the Chemistry Education area (SIMPEQUI)s, bringing an explanation of the difficulties related to the act of teaching and learning the discipline of Chemistry when having students in the context with Hearing Impairment. We chose to explain the research that addresses this theme, based on specific points that they report, identifying teaching strategies in order to solve this theme. The research is of a bibliographic nature and was carried out during meetings of the authors, in order to awaken in undergraduates the necessary relationship between professional teaching involved in research and practice. It was found that, from a temporal state of 15 years of SIMPEQUI(s) - (2006-2021), 22 works involving Chemistry Teaching and Hearing Impairment were registered. As main difficulties in relation to learning, registered in the research we have. Poor training of tutors, teachers and interpreters of Libras and the absence of Signs for the understanding of certain Contentos that are in the Curriculum grid of the discipline, as the main strategy to solve the problem, the analyzed works cite the dialogic relationship and together between the teacher of Chemistry and the Libras Interpreter. This work contributes, as a strategy to solve this problem, established through readings, is teacher autonomy, developed through boldness, search, readings and re-readings of research that work with this theme.